2012
DOI: 10.1186/1758-2946-4-31
|View full text |Cite
|
Sign up to set email alerts
|

Drug-likeness analysis of traditional Chinese medicines: 1. property distributions of drug-like compounds, non-drug-like compounds and natural compounds from traditional Chinese medicines

Abstract: BackgroundIn this work, we analyzed and compared the distribution profiles of a wide variety of molecular properties for three compound classes: drug-like compounds in MDL Drug Data Report (MDDR), non-drug-like compounds in Available Chemical Directory (ACD), and natural compounds in Traditional Chinese Medicine Compound Database (TCMCD).ResultsThe comparison of the property distributions suggests that, when all compounds in MDDR, ACD and TCMCD with molecular weight lower than 600 were used, MDDR and ACD are s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
60
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(60 citation statements)
references
References 38 publications
0
60
0
Order By: Relevance
“…For example, our studies showed that Rule-of-Five is not a good predictor to estimate intestinal absorption, and even less reliable than a simple molecular property, topological polar surface area (TPSA) [58,59]. In 2012, we evaluated the performances of Rule-of-Five and Opera's filters to distinguish the drug-like molecules in MDDR from the non-drug-like molecules in ACD [50]. Two MDDR and ACD subsets with similar MW distributions were generated artificially.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…For example, our studies showed that Rule-of-Five is not a good predictor to estimate intestinal absorption, and even less reliable than a simple molecular property, topological polar surface area (TPSA) [58,59]. In 2012, we evaluated the performances of Rule-of-Five and Opera's filters to distinguish the drug-like molecules in MDDR from the non-drug-like molecules in ACD [50]. Two MDDR and ACD subsets with similar MW distributions were generated artificially.…”
Section: Introductionmentioning
confidence: 98%
“…That is to say, when drug-like and non-drug-like compounds have similar MW distributions, Rule-of-Five does not have any prediction capability to distinguish drug-like from non-drug-like molecules. We also applied the Opera's RNG and RGB filters to evaluate the ACD and MDDR subsets with similar MW distributions, and most non-drug-like molecules in ACD (59.5%) were identified to be drug-like [50]. Recently, Ritchie et al evaluated the correlations between the QED score and the actual pharmaceutical and pharmacokinetic (PK) profiles in humans for 300 oral drugs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…macrofocus.com/) were used to analyze the structural diversity. Scaffold architectures were first clustered using ECFP_4 fingerprints by the cluster molecules component in Pipeline Pilot with the average number of compounds per cluster was set to 50 [32]. Then, the scaffold cluster number as well as its frequency were utilized to categorize scaffolds by circles of different area and colors [31].…”
Section: Scaffold Countsmentioning
confidence: 99%
“…The chemical space diversity of all the databases was evaluated to ensure an adequate novelty not only from the 2D physiochemical properties aspect but also from the scaffold and structural diversity perspectives. The latter were explicated through the count of scaffolds, cumulative scaffold frequency plot (CSFP), P n values as well as tree maps visualization [31,32]. Simultaneously, Bayesian models were constructed using VEGFR-2 actives and decoys from the directory of useful decoys enhanced database (DUD-E) [33] database and their reliability was validated using internal [16,19,22].…”
Section: Introductionmentioning
confidence: 99%